The effect of high fiber beverages consumption on anthropometric, defecation and quality of life changes in overweight / obese female volunteers - Hudthagosol, Chatrapa (Food and Applied Bioscience Journal, 2022)
Overweight status and obesity are major risk factors that cause noncommunicable diseases and lower quality of life. Currently, rice germs can be a source of dietary fiber which is the main ingredient for the production of the dietary fiber drinks. This study aimed to determine the effect of high fiber beverages consumption on anthropometric, defecation and quality of life changes among overweight/obese female volunteers. A randomized controlled trial with two parallel groups (control group = 18, experimental group = 18), were conducted for 12 weeks. Anthropometrics included body weight, BMI and body fat percentage (the total mass of fat divided by total body mass, multiplied by 100). Defecation was assessed using the Bristol Stool Form Scale−7. Quality of life was assessed using the WHOQOL−BREF−THAI−26 questionnaire. Fecal appearance and quality of life were analyzed using Chi−square tests (SPSS Software, Version 18; SPSS Inc., Chicago, IL, USA). At week 12, the experimental group had a significantly lower body fat percentage than the control group (P−value = 0.040). Within experimental groups, the average fat body percentage was decreased (P−value < 0.05) at weeks 4, 8 and 12 but did not differ in the control group. The experimental group had a higher average frequency of defecation than the control group and significantly increased frequency in the experimental group (P−value < 0.05). Experimental and control groups correlated regarding quality of life overall at week 12 (P−value = 0.004) with 65 and 20% good quality of life, respectively. The group of high fiber beverages intake (a) reduced the body fat percentage (b) increased the average frequency of defecation and (c) correlated with quality of life concerning better physical health.